The Iranian revolution and the Arabs: The quest for Islamic identity and the search for an Islamic system of government - Tibi, Bassam (Arab studies quarterly, 1986)
The first part of this paper focuses on the concept of cultural identity in a changing world and concludes, that in reality there is no unique, invariable Islamic identity for all Muslims. The second part grapples with the problem of Islamic government, and the third section presents Arab reactions to the Iranian claim of being vanguard of Islamic "ummah", i.e., of providing a political lead for the Arabs also. (DÜI-Hns)